1999
DOI: 10.1021/ie980495p
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated Vitreous Carbon Electrode for Copper(II) Removal from Dilute Acid Solutions:  Effect of the Dissolved Oxygen

Abstract: Reticulated vitreous carbon 45 pores per inch is adopted to deposit copper(II) from dilute solutions of 10-20 ppm to below 1 ppm. Three working potential values are tested: E ) -0.4 V and E ) -0.5 V, at which metal deposition is under diffusion control, and E ) -0.25 V, at which the effect of O 2 reduction is limited, but deposition does not occur at its maximum rate. A theoretical model, which takes into account the reabsorption of O 2 from air, is proposed to interpret the trend of faradic yield as the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Polcaro et al [45] reported on the effect of dissolved oxygen in the removal of copper from dilute acid solutions. They presented a mathematical model to interpret the influence of O 2 during copper deposition and concluded that an increase in flow rate enhanced the current for copper deposition, (a logical consequence of mass transport control).…”
Section: Copper Depositionmentioning
confidence: 99%
“…Polcaro et al [45] reported on the effect of dissolved oxygen in the removal of copper from dilute acid solutions. They presented a mathematical model to interpret the influence of O 2 during copper deposition and concluded that an increase in flow rate enhanced the current for copper deposition, (a logical consequence of mass transport control).…”
Section: Copper Depositionmentioning
confidence: 99%
“…A generic schematic of the experimental apparatus described in all the papers analyzed herein is shown in Figure 3 , while Figure 4 shows an example of the porous 3-dimensional RVC cathode on which the depletion process is based. Further details are reported in papers [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…A generic schematic of the experimental apparatus described in all the papers analyzed herein is shown in Figure 3, while Figure 4 shows an example of the porous 3-dimensional RVC cathode on which the depletion process is based. Further details are reported in papers [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]50]. Despite the experimental setup being almost the same in all the cases taken into account, it seems that even slight differences, together with the peculiar features of each ionic species, can produce quite different results [31][32][33][34][35][36][37][38]44,46,50].…”
Section: Experimental System Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been recently a considerable increase of publications, which shows that there is a pressing necessity of intensification of leach processes of nonferrous metals due to complicating of refinable raw materials. Electrodes (Friedrich and Snell, 2004) and nonorganic and organic solutions (Leaist et al, 1989;Polcaro et al, 1999;Tangirala et al, 2010) are used to accelerate dissolution of nonferrous metals.…”
Section: Literature Reviewmentioning
confidence: 99%